Earthworm Population Density in Sugarcane Cropping System Applied with Various Quality of Organic Matter - Nurhidayati Nurhidayati; Endang Arisoesilaningsih; Didik Suprayogo; Kurniatun Hairiah (Journal of Tropical Life Science, 2012)
Earthworms population in the soil are greatly impacted by agricultural management, yet little is known about how the quality and quantity of organic matter addition interact in sugarcane cropping system to earthworm population. This study describes the effect of various organic matter and application rates on earthworms in sugarcane cropping system. Earthworms were collected in April, July and December from 48 experimental plots under five kinds of organic matter application : (1) cattle manure, (2) filter cake of sugar mill, (3) sugarcane trash, (4) mixture of cattle manure+filter cake, and (5) mixture of cattle manure+sugarcane trash. There were three application rates of the organic matter (5, 10, and 15 ton ha-1). The treatments were arranged in factorial block randomize design with three replications and one treatment as a control (no organic input). Earthworms were collected using monolith sampling methods and hand-sorted from each plot, and measured its density (D) (indiv.m-2), biomass (B) (g m-2) and B/D ratio (g/indiv.). All the plots receiving organic matter input had higher earthworm density, biomass, and B/D ratio than the control. The highest earthworm population density was found in the plot receiving application of sugarcane trash (78 indiv.m-2) and the mixture of cattle manure+sugarcane trash (84 indiv.m-2). The increase in application rates of organic matter could increase the earthworm density and biomass. Earthworm population density also appeared to be strongly influenced by the quality of organic matter, such as the C-organic, N, C/N ratio, lignin, polyphenols, and cellulose content. Earthworm preferred low quality organic matter. It was caused by the higher energy of low quality organic matter than high quality organic matter. Our findings suggest that the input of low quality organic matter with application rate as 10 ton ha-1 is important for maintaining earthworm population and soil health in sugarcane land.Keywords: earthworms, organic matter quantity, quality, sugarcane cropping system